2017
DOI: 10.20452/pamw.4156
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-27 (IL-27) in the lower airways diseases. Increased levels of IL-27 in early clinical stages of non-small cell lung cancer (NSCLC) patients

Abstract: INTRODUCTION    Interleukin 27 (IL‑27) is a cytokine secreted mostly by antigen‑presenting cells. It is important for the immune polarization of T helper‑1 (Th1) cells, and its role in interstitial lung diseases (ILDs) and lung cancer has been investigated. OBJECTIVES    We assessed IL‑27 expression in the lower airways of patients with selected ILDs and early‑stage non-small cell lung cancer (NSCLC). PATIENTS AND METHODS    IL‑27 concentrations were examined by an enzyme‑linked immunosorbent assay in bronchoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…NSCLC patients with higher sRANKL 52 or BCA-1 53 levels in BALF were associated with poorer survival. Another study also demonstrated a significant rise in the level of IL-27 expression in the BALF of early NSCLC patients 56 . Researchers have only demonstrated relevant evidence for the above indicators but have not conducted in-depth studies, which is insufficient for clinical practice.…”
Section: Application Of Balf In the Diagnosis And Prognosis Of Lung C...mentioning
confidence: 91%
“…NSCLC patients with higher sRANKL 52 or BCA-1 53 levels in BALF were associated with poorer survival. Another study also demonstrated a significant rise in the level of IL-27 expression in the BALF of early NSCLC patients 56 . Researchers have only demonstrated relevant evidence for the above indicators but have not conducted in-depth studies, which is insufficient for clinical practice.…”
Section: Application Of Balf In the Diagnosis And Prognosis Of Lung C...mentioning
confidence: 91%
“…Although BAL drains a relatively large area surrounding a lung tumor and, therefore, the diagnostic yield is hypothetically not dependent on a bronchus leading to it, the diagnostic usefulness of BAL is unacceptably low with a reported sensitivity for the diagnosis of lung cancer of 29% when only cytological analyses are considered [13]. However, with the upcoming interest in ICIs, BAL gained new attention as a tool to access TME surrounding a lung cancer [14][15][16][17][18][19][20][21][22][23]. With our study, we aimed to investigate TME of lung cancer by analyzing various cytokines in BALF and thus answering three questions:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the expression profile of IL gene may also be one of the vital markers of early pathological changes, occurrence and progression of cancer. 4 , 5 Currently, studies on the expression of IL27 in cancer are still extremely limited. Our work comprehensively and systematically studied the IL27 gene expression in the generic cancer when compared with the existing IL27 gene related research experiment.…”
mentioning
confidence: 99%